What Factors Drive Childhood Stunting? Examining Child Health Risks, Maternal and Early-Life Determinants, Nutrition, and Socioeconomic Influences - Barkah, Asep; Usep, Usep; Sony, Ujang; Nugraha, Dani; Amin, Kamaludin Firdaus; Lestari, Vega; Fauzi, Achmad (Journal of Applied Nursing and Health, 2026)
Background: Childhood stunting remains a major global public health challenge driven by complex interactions among child health risks, nutritional status, maternal and early-life determinants, and socioeconomic conditions. Although the literature on stunting has expanded substantially, a comprehensive bibliometric mapping focusing on immunization, nutrition, and maternal determinants remains limited. This study aimed to map global research trends, thematic structures, and collaboration networks related to childhood stunting determinants. Methods: This study employed a bibliometric analysis of Scopus-indexed publications. Data were retrieved from the Scopus database in January 2026 using search terms related to childhood stunting, immunization, nutrition, and maternal factors. Eligible documents included journal articles and review articles published between 2010 and 2026 in English. After screening and data cleaning, 323 documents were included for analysis. Bibliometric indicators were analyzed using VOSviewer version 1.6.20, including publication trends, keyword co-occurrence, co-authorship networks, and thematic clustering. Results: The findings showed a growing volume of publications on childhood stunting determinants over time, indicating increasing global scholarly attention. Keyword co-occurrence analysis identified four major thematic clusters: child health risk factors, maternal and early-life determinants, socioeconomic influences, and nutritional status and malnutrition. The term “stunting” emerged as the central keyword with strong links to child health, maternal nutrition, breastfeeding, poverty, and sanitation. The results indicate that stunting research has evolved into an interdisciplinary field integrating biological, maternal, environmental, and structural perspectives. Conclusion: Research on childhood stunting has developed within an increasingly multidimensional and collaborative scientific landscape. Bibliometric mapping highlights the need for integrated research and policy strategies that connect maternal care, nutrition interventions, immunization services, and socioeconomic support. Future studies should strengthen cross-country collaboration, expand interdisciplinary approaches, and address research gaps in low- and middle-income settings.